A unique formulation of sodium bicarbonate buffered pantoprazole powder for oral suspension: perspectives from an active controlled cross-over bioequivalence study - Prasad, Virukalpatti Gopalratnam Mohan; Chatterjee, Anindita; Vaddem, Radhakrishna; Sharma, Akhilesh D. (International Journal of Advances in Medicine, 2022)
Background: The aim was determining bioequivalence between pantoprazole buffered powder for oral suspension and pantoprazole enteric coated tablets under fasting conditions in healthy volunteers. Methods: In randomized cross-over study, participants were administered a single oral dose of pantoprazole powder as suspension 40 mg (sodium bicarbonate as buffer) or one enteric coated tablet of pantoprazole 40 mg, with 240±2 ml of water as per the randomization schedule in each study period. Blood samples were collected at pre-dose and at 0.33, 0.67, 1, 1.33, 1.67, 2, 2.33, 2.67, 3, 3.33, 3.67, 4, 4.5, 5, 5.5, 6, 7, 8, 9, 10, 12, 14, 16 and 24 hours post-dose. Plasma concentration of pantoprazole was determined with LC-MS and various pharmacokinetic parameters like Cmax, AUC0-t, AUC0-inf were compared between test and reference groups. Results: Amongst 41 subjects, Cmax (3752.4±1084.6 vs. 3521.7±1099.5 ng/ml) was achieved higher in less Tmax time (1 (0.28) vs. 2.3 (0.83) hrs) with test drug as compared to reference drug. The ratios of geometric least square mean and its 90% confidence interval on log transformed Cmax, AUC0-t and AUC0-inf for pantoprazole fall within the acceptance criteria of 80% to 125%. No adverse events were observed. Conclusions: Pantoprazole powder for oral suspension 40 mg (sodium bicarbonate as buffer) was well tolerated and bioequivalent with pantoprazole enteric coated tablets IP 40 mg in terms of rate and extent of absorption under fasting conditions. At same time, the shift in AUC to the left with reduction in Tmax with the new formulation is suggestive of faster rate of absorption.